Economic Crisis and Fiscal Reforms in Latin America - Mark Hallerberg; Carlos Scartascini (Inter-American Development Bank (IDB), 2011)
The recent financial crisis has initiated pressures for not only policy reform but also fundamental institutional fiscal reforms. This paper explores the connection between economic crises and fiscal institutional reforms in a region that has experienced plenty of both in recent years, namely Latin America. For that purpose it reviews the literature and provides five hypotheses about why, and under what circumstances, crises would promote reforms. The empirical evidence shows that debt crises make reforms more likely but banking crises on their own, if anything, reduce the pressure for fiscal institutional reforms. Political institutions are also important. If the electoral system encourages the personal vote, the country is more likely to reform. This evidence may become useful for predicting the likelihood of reforms in the developed world.
Keywords: C93; I21; 330; Information and communications technology; Education; Experimental design; Ecuador